Strategy of the Principal of MTs.S PP. Darussalam Kunir in Successful Accreditation of Excellence - Shely Kusumasari; Ferianto; Aminuddin; Sulhah Habibah; Ahmad Farihin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article aims to analyze the implementation of principal strategies in MTs.S PP educational institutions. Darussalam Kunir in achieving superior accreditation. This research method was obtained from written sources related to management strategy. The research method used in this article is descriptive qualitative data. The data collection technique in this research is environmental observation, interviews. Environmental observations and literature studies collected books and journals related to strategic management, school principal leadership, and the keys to successful accreditation. This analysis technique is in the form of a narrative. Strategic management is a way for an institution or organization to achieve goals which also require the role of a leader with a leadership spirit who can influence the performance/behavior of other people. Implementation of accreditation is carried out through activities comparing the condition of schools in activities to meet the four standards set during the accreditation period which will be carried out in the 2023-2024 academic year. Therefore, the school principal plays a very important role in implementing a series of school principal strategies to implement strategic management to make accreditation successful at MTs.S PP. Darussalam Kunir.